Actor Analysis in Resolving Social Violence in The Mining Area of Kolaka Regency, Southeast Sulawesi Province - Suliamin Kasnar Sul; Sofyan Sjaf; Hermanto Siregar; Sri Mulatsih (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2024)
Actor participation has a significant impact on dealing with social violence because they possess the resources and abilities required to intervene and address social violence effectively. Actors with substantial resources can influence policies aimed at resolving, preventing, and enhancing community capacity in handling social violence. Therefore, it is crucial to conduct an analysis and mapping of actor resources in order to identify the strengths of each actor in the mining area of Kolaka Regency, Southeast Sulawesi Province. The method used is the Casey index to measure the actor capital index, and the Promethee analysis tool is used to rank actor capital and analyze the strengths and weaknesses of actor capital. The results of data processing found that the actors who play a role in overcoming social violence in the mining area of Kolaka Regency have the status of Village Head, Bhabinkabtibmas (Police), Babinsa (Army), and Community Leaders. The status of Village Heads tends to have quite high levels of social, economic, and human resource capital but low cultural capital. The author recommend that the government strengthen the capacity of village heads in handling conflicts and create Village Regulations regarding conflict resolution and social violence based on local cultural wisdom.